Inhibiting Effect of Poly-4-Vinylpyridine on the Acid Corrosion of Copper - Khalifa, O.R.; Abdul Hamid, I.A.; Mokhtar, S.M.; Kassab, A.A. (Asian Journal of Chemistry, 2010)
The efficiency of poly-4-vinylpyridine (poly-4-VP) as an inhibitor for acid corrosion of Cu was investigated. The effect of poly-4-VP on the corrosion rate was measured in 3 M HNO3 at various temperatures and concentrations. It was observed that poly-4-VP has a significant inhibiting effect on the corrosion of the metal; protection efficiencies approaching 80% were measured. The result of the apparent activation energies in absence and in presence of the inhibitor suggest that poly-4-VP does not change the mechanism of the rate-determining step of the corrosion process. The mechanism of inhibition was proposed on the basis of the formation of a protective film by poly-4-VP molecules on the metal surface.